Development of an electronic nose for detection and discrimination of exhaled breath of hepatocellular carcinoma patients - Thara Seesaard (2018)
An electronic nose (E-nose) has been designed and fabricated for detection of liver cancer based on measurement of the volatiles in the exhaled breath. This e-nose system is in the form of a briefcase, practical for adoption in both clinical and on field uses. The sensing unit is based on eight commercial metal oxide semiconductor gas sensors that are sensitive to a broad range of volatile chemicals, such as ammonia, sulfides, alcohol and hydrocarbons, sufficient to cover the chemical species contained in the human exhaled breath. Delivery of the odor samples to e-nose can be done easily by collecting the exhaled molecules from face mask worn by patients for several minutes. We have demonstrated the preliminary performance of this portable e-nose by comparing the odor of the breath based on two groups of people, patients diagnosed with hepatocellular carcinoma (HCC) and healthy control. It was found that this e-nose can discriminate the patterns of volatile organic compounds (VOCs) from these two groups, as analyzed by the principal component analysis (PCA). With further validation and development, this e-nose may become very useful for monitoring the exhaled as a screening device for detecting patients with early stage liver cancer. Such a device would help reduce the high mortality associated with this disease. © 2012 IEEE.